2017
DOI: 10.6000/1929-4247.2017.06.04.1
|View full text |Cite
|
Sign up to set email alerts
|

Home Environment Characteristics and BMI Z-Score Among Saudi Preschool Children: A Feasibility Study

Abstract: Objective: To assess feasibility of using preschools in Saudi Arabia as a source for collecting nutrition-related data; To examine associations among home environment characteristics and child BMI z-score (BMIz). Methods: Fifty-three (3-5 years old) children and their mothers were recruited from two preschools in Jeddah, Saudi Arabia. Mothers completed a self-administered questionnaire. Child anthropometry was completed using standardized procedures. BMIz was calculated using the WHO growth standards and refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Only two studies assessed child body mass index (BMI) as a correlate of SB. Although one study observed no significant association between BMI and TV time, 45 one reported that higher BMI was associated with more time spent on SB out of school hours but not with objectively measured total SB 36 …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Only two studies assessed child body mass index (BMI) as a correlate of SB. Although one study observed no significant association between BMI and TV time, 45 one reported that higher BMI was associated with more time spent on SB out of school hours but not with objectively measured total SB 36 …”
Section: Resultsmentioning
confidence: 96%
“…One study from China reported that longer outdoor playtime and active commuting to school (e.g., walking) were associated with less objectively measured total SB time 36 . Another two studies examined physical activity, 45 sleep time, 38 imitation of televised models, and beginning age for TV viewing 38 . They reported insignificant associations with SV time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the whole family, the role of the fathers and siblings are usually neglected, where more pressure is carried on mothers. A recent study carried by Mosli showed that paternal involvements results in higher BMI of the child, unlike when mothers were college graduates and more knowledge, a lower BMI of children were seen [47]. In addition, Mosli et al, 2015 have proved that siblings have an impact on the last born child's health and nutrition, where a positive association with overweight and obesity was seen.…”
Section: Journal Of Food and Nutrition Researchmentioning
confidence: 99%